TELAAH AGAMA, KONSEP BARU PENDIDIKAN ISLAM DAN SAINS - Ahmad Khori (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2016)
This paper is intended to examine the Islamic sciences that have big chance to be integrated with science through the practice of Islamic education. This is done so Islam will be able to re-concern about science vision such it happened in the early days of Islam. There are several models offered of contemporary Muslim scientific epistemology which have big influence among the Islamic world. Some existing offers is the need for shifting the paradigm in the field of Islamic scientific epistemology, namely from Islamic epistemology normative-textual-bayani to the contemporary Islamic scientific epistemology in intuitive-spiritual-Irfani pattern (in axiological) that have many relationship with ethical dimensions to the development of science. Moreover, it needs a redefinition or reconceptualization of the discourse of science in the Islamic world.